Influence of complement on neutrophil extracellular trap release induced by bacteria. (21st April 2015) - Palmer, L. J.; Damgaard, C.; Holmstrup, P.; Nielsen, C. H.
Abstract : Background and Objectives: Neutrophil extracellular trap (NET) release has generally been studied in the absence of serum, or at low concentrations of untreated or heat‐inactivated serum. The influence of serum complement on NET release therefore remains unclear. We examined the DNA release induced by Staphylococcus aureus and three oral bacteria: Actinomyces viscosus, Aggregatibacter actinomycetemcomitans and Fusobacterium nucleatum subsp. vincettii . Material and Methods: Bacteria‐stimulated NET release from the neutrophils of healthy donors was measured fluorometrically. Various complement containing and complement blocking conditions were used, including heat inactivation of the serum and antibody blockade of complement receptors 1 (CR1, CD35) and 3 (CR3, CD11b/CD18). Results: While the presence of serum markedly enhanced NET release induced by S. aureus, A. actinomycetemcomitans, and to a lesser extent by A. viscosus, there was no enhancement of NET release induced by F. nucleatum . The serum‐mediated enhancement of NET release by A. actinomycetemcomitans was neutralized by heat inactivation of serum complement, while this was not the case for S. aureus . Blockade of CR1, significantly reduced NET release induced by S. aureus, A. actinomycetemcomitans and A. viscosus, while blockade of CR3, had no effect. However, opsonization of S. aureus with antibodies may also have contributed to the enhancing effect of serum, independently of complement, in that purified IgG promoted NET release. Conclusions: In conclusion, complement opsonization promotes NET release induced by a variety of bacteria, including A. actinomycetemcomitans, and CR1 plays a dominant role in the process. Complement consumption or deficiency may compromise NETosis induced by some bacterial species, including A. actinomycetemcomitans . Within biofilms, the complement‐inactivating abilities of some bacteria may protect other species against NETosis, while these are more vulnerable when adopting a planktonic lifestyle.